Two case reports of MDA5-type seronegative dermatomyositis - Lauren C Balogh; Airiss R Chan; Elaine A Yacyshyn; Robert Gniadecki (SAGE Open Medical Case Reports)
Dermatomyositis (DM) is an autoimmune idiopathic inflammatory myopathy with characteristic dermatologic manifestations. Myositis-specific autoantibodies (MSAs) delineate DM subtypes and their prognoses. Uncommonly, patients present with distinct clinical features of DM, including photosensitive dermatitis, heliotrope rash, Gottron’s papules, and nailfold changes; however, their autoimmune serology is negative for expected MSAs. Herein, we describe two unconventional cases of seronegative, amyopathic MDA5-DM and offer potential explanations, including fluctuating antibody levels, non-MSA pathophysiology, and limitations in current immunoassays.